Pengaruh Biaya Produksi dan Harga Jual Terhadap Pendapatan Pada UMKM Kolam Pancing Bado Tanjung Morawa - Nurul Nasiyra; Vidya Fathimah (CIVITAS: Jurnal Studi Manajemen, 2022)
This study aims to determine whether there is an effect of Cost Of Productions and Selling Prices on Income at Bado Fishing Pond In Tanjung Morawa for the 2017-2020 period. The results showed that the coefficient of determination test (R2) obtained a result of 0.958 or 95.8% indicating that the variables of cost of produstions and selling price were able to explain the variations that occur in the income at Bado Fishing Pond, while the remaining 4.2% is explained by other variables not examined. The results of the partial study of cost of productions have positive and significant effect on the income, meanwhile selling price have negative effect significant on the income at Bado Fishing Pond. Meanwhile, the results of simultaneous testing of cost of productions and selling price together have a significant and significant effect on the income at Bado Fishing Pond in Tanjung Morawa.